Factors affecting the outcome of vestibular rehabilitation in patients with peripheral vestibular disorders. Issue 6 (December 2022) - Ogihara, Hirofumi; Kamo, Tomohiko; Tanaka, Ryozo; Azami, Masato; Kato, Takumi; Endo, Mayumi; Tsunoda, Reiko; Fushiki, Hiroaki
Abstract: Objective: Previous studies have reported that developmental, environmental, medical, psychological, visual, and other sensory-related factors can influence the outcome of vestibular rehabilitation. However, only a few studies have used patient's daily lives as the main outcome. In addition, in some studies, rehabilitation was not supervised by a physical therapist. This study aimed to determine the factors associated with the outcome of physical-therapist-supervised vestibular rehabilitation in patients with peripheral vestibular disorders, with the impact of dizziness on quality of life as the main outcome. Methods: This retrospective cohort study included 47 patients with peripheral vestibular disorders. A physical therapist provided 40 min of vestibular rehabilitation once a week for 4 weeks. Age, sex, disease duration, Dizziness Handicap Inventory (DHI), Timed Up-and-Go test (TUG), Dynamic Gait Index (DGI), Functional Gait Assessment (FGA), Activity-Specific Balance Confidence Scale (ABC scale), and Hospital Anxiety and Depression Scale (HADS) were investigated. Multiple regression analysis was performed, with the DHI rate of change before and after the intervention as the objective variable. Results: Vestibular rehabilitation improved all outcomes. In the multiple regression analysis, the ABC scale was identified as a factor that significantly influenced the DHI rate of change (β = -0.428, p < 0.01). Conclusion: A higher ABC scale score was associated with a lower DHI rate of change (i.e., better improvement). Therefore, it may be important to assess psychological aspects, especially confidence in balance, when implementing vestibular rehabilitation in patients with peripheral vestibular disorders.